Identification of anti-mouse PD-1 agonist antibodies that inhibit T cell activation - Liu, Lingling; Takashima, Shoma; Tokumaru, Yosuke; Ikuta, Naoko; Nakajima, Yuka; Ohta, Akio (Frontiers in Immunology, 2025)
PD-1-stimulating agents have been projected to be unique immunosuppressants for the treatment of undesirable inflammatory conditions including autoimmune diseases. We recently characterized anti-human PD-1 (hPD-1) agonist antibodies, which showed a significant immunosuppressive effect in hPD-1 knock-in mice. However, the lack of anti-mouse PD-1 (mPD-1) agonist antibody has been a limitation in testing the efficacy of PD-1-targeted therapy using various disease models. To find mPD-1 agonist antibody, we assessed biological activities of commercial anti-mouse PD-1 mAb clones. Agonist activity was evident in RMP1-30, which did not block PD-1-PD-L1 interaction. In contrast, 29F.1A12 was the exceptionally strong blocking antibody. Interestingly, RMP1–14 was a dual-function antibody offering decent blocking activity and the agonist activity comparable to RMP1-30. In this assessment, PD-1 expression levels critically affected both blocking and agonist activities. T cells expressing PD-1 at higher levels were stronger responders in the agonist assay, while cells with lower PD-1 expression were more sensitive in detecting blocking activities. Considering physiologically-relevant PD-1 levels, RMP1–14 would substantially behave as a blocker in vivo consistent with its frequent use to enhance anti-tumor immunity. Taken together, RMP1–30 may be useful as mPD-1 agonist antibody although its in vivo efficacy may vary dependent on the local Fc receptor availability and PD-1 levels on target cells. It should be also noted that in vivo use of this rat IgG2b clone may require attention to the mechanism of immunosuppression that may involve PD-1 agonism and the depletion of PD-1-expressing effector cells.